2015
DOI: 10.1186/s12913-015-1213-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of peers, community lay persons and Village Health Team (VHT) members improves six-week postnatal clinic (PNC) follow-up and Early Infant HIV Diagnosis (EID) in urban and rural health units in Uganda: A one-year implementation study

Abstract: BackgroundEffective Prevention of Mother to child Transmission of HIV (PMTCT) relies heavily on follow-up of HIV-infected women and infants from antenatal, through postnatal, to the end of the breastfeeding period. In Uganda, postnatal (PNC) follow-up remains below 50 % creating a missed opportunity for linkage to comprehensive HIV care and early infant diagnosis (EID). We evaluated the use of HIV infected peer mothers (peers), community lay persons and Village health team (VHT) members to improve PNC follow u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 7 publications
3
42
1
Order By: Relevance
“…This process ensured that women would get essential information and not get lost between and within PMTCT/PNC and FP clinics. These results support evidence from previous studies that in busy settings with low services utilization, peer mothers’ involvement contributes to increased PMTCT services uptake [25, 26]. …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This process ensured that women would get essential information and not get lost between and within PMTCT/PNC and FP clinics. These results support evidence from previous studies that in busy settings with low services utilization, peer mothers’ involvement contributes to increased PMTCT services uptake [25, 26]. …”
Section: Discussionsupporting
confidence: 91%
“…The utilization of peers can offer an affordable and feasible task shifting solution to address frequently missed FP opportunities among HIV infected women attending PMTCT/PNC clinics. Our findings are supported by evidence from a previous study conducted at our site, that demonstrated that employing HIV-infected peers compared to community lay persons was more effective in increasing the six-week postnatal follow up of HIV-infected mothers and the early HIV testing of their infants [25]. Earlier studies and programs carried out in Uganda and Malawi, also found that use of peer mothers/educators helped in improving knowledge and retention in long-term HIV care among women living with HIV [26, 32].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…HIV remains a major challenge globally regardless of decades of advocacy and investment in programs to control the spread of the virus [4, 5]. Globally, an estimated 35.3 million people were living with HIV in 2012 [6, 7]. The number of newly infected children in 2012 was 260,000 in low- and middle-income countries [7].…”
Section: Introductionmentioning
confidence: 99%
“…Male involvement is said to be very low in many health facilities in Ethiopia and it is one of the potential program gaps unfavourably affecting PMTCT services uptake in the country [18]. For this reason, previously in a country it was highlighted as involving male partners in ANC/PMTCT can often be utilized as an entry point for the provision of additional PMTCT services notably partner testing, condom use, and infant feeding recommendations for both male and female participants [6, 14]. …”
Section: Introductionmentioning
confidence: 99%